Analisis pengaruh pengungkapan sustainability report, kinerja keuangan, dan kinerja lingkungan terhadap nilai perusahaan - Aristha Purwanthari Sawitri; Nurcholis Setiawan (Journal of Business & Banking, 2017)
The goal of peneliitian is to look at the effect of disclosure of the sustainability report, the financial performance and environmental performance of companies. The sample of this research is a company entered in the index 30 in 2012 until the year 2016 and sampling method using a purposive sampling. The results of this study found that the sustainability report has no effect against the value of the company, the same result in-show by a variable performance environment where environmental performance does not affect the value of the as for the company's financial performance variables have significant influence towards the value of the company.